The Effectiveness of the Eco-Pentren Program and the SampahKita App in Environmental Conservation at Mambaul Ulum Bata-Bata - Ira Suharwati, Sri; Moh. Ihsan Zain, Fadolul Ghafur; Zain, Moh. Ihsan (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
The level of public awareness regarding environmental sustainability, particularly in waste management at Mambaul Ulum Bata-Bata, remains relatively low. The gap between theoretical understanding and practical application in the field is an issue that must be addressed. To address this issue, the Eco-Pentren program can be implemented, along with the use of the SampahKita app in partnership with the Hamdalah waste management service. This study employs a quantitative approach using data collection techniques such as pre-test and post-test assessments, as well as documentation. The study sample consists of 43 students/pupils from Mambaul Ulum Bata-Bata selected at random. Data were analyzed using frequency distributions with the aid of basic SPSS. The research results indicate that the implementation of the Eco-Pentren program and the SampahKita app proved effective at a rate of 72.1%. It was deemed effective due to changes in student behavior, including active participation in the â€œClean Morningâ€ and â€œBlessed Friday (School Cleanup)â€ programs as well as their practice of the 5R principles, maggot farming, active participation in scientific writing activities on environmental themes, and the formation of a special task force (LHB Task Force) whose members consist of administrators and religious instructors who address environmental issues in a structured manner.